SOCIOECONOMIC DYNAMICS AND ENVIRONMENTAL HEALTH OUTCOMES IN INFORMAL SETTLEMENTS OF PORT HARCOURT, NIGERIA - Immaculata NWOKORO; Taibat LAWANSON; Olufunke EBUEHI; Samson FADARE; John AGWU; Oluwole SOYINKA (Journal of Construction Project Management and Innovation)
Although many studies have shown strong evidence of a direct relationship between the human environment and health, they have been too generic in nature, concentrating on community patterns and largely ignore the link between environmental health outcomes and specific socioeconomic indices manifesting at the household level. This study, therefore, seeks to understand the interface between household socioeconomic indices and the urban environment in six informal coastal settlements of Port Harcourt Nigeria. It further examined how these interactions affect environmental health. It questions the extant belief that living in a deprived neighbourhood is bad for one’s health, hence the focus on the households level. Issues examined include housing and environmental conditions like sources of water, sanitation methods, drainage conditions and quality of toilet and kitchen facilities as well as socio-economic characteristics such as age, gender, income and household size. Health seeking behaviour and recent self-reported illnesses associated with poor environmental conditions were also considered. Data collection was by mixed methods integrating simple random sampling on household heads as well as focus group discussion with community leaders in Andoni, Bundu, Captain Amangala, Emenike, Marine Base and Rex Lawson communities respectively. Data analysis was by simple descriptive statistics as well as chi square test of relationships. Major results show that even though environmental and housing conditions across the selected communities were in deplorable conditions, socio-economic status, especially educational level of the household head, had a significant influence on health seeking behaviour. Furthermore, sanitation related diseases (diarrhoea, typhoid and cholera) were the most prevalent, directly attributable to the poor environmental conditions. The  tudy concludes by advocating for community driven urban renewal efforts aimed at improving access to urban basic services including education and health infrastructure. It further advocates for an interface of the formalinformal governance structures in order to find a mutually beneficial solution to the hitherto almost neglected people of the informal squatter waterfront settlements of Port Harcourt waterside communities.